Indigo [videorecording (DVD)] - Simon, Stephen, 1946-; Walsch, Neale Donald; McCandless, Meghan; Bowman, Dane (Monterey Video, 2005)
The inspirational story of a lonely old man and his granddaughter, an 'Indigo' child. The term refers to a child blessed with the ability to foresee events, see things that are not evident to others, and heal with a special power not possessed by adults.